PENGEMBANGAN LEMBAR KERJA SISWA BIOLOGI SMA BERBASIS PENDEKATAN ILMIAH UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR SISWA - Evi Suryawati (Jurnal Pendidikan Biologi, 2015)
This research aimed to develop students worksheet based scientific approaches on senior high school.  This study consisted of three phases: analysis, design and development. The worksheets focused on improving the thinking skills of students grade X, XI and XII. Grade X on the material change and environmental conservation focused on Higher Order Thinking Skills (HOTS), grade XI on organ systems focused on Critical Thinking Skills, and grade XII on biotechnology materials focused on Creative thinking skills. Simulation test conducted at the Biology Education Laboratory of the University of Riau The scoring of worksheets validated by internal and external validator. Then pilot test on MAN 2, SMA Babussalam, and SMAN 8 Pekanbaru.  The Results of the assessment showed that wosksheets based scientific approach has a very valid and valid category that consist a pedagogical aspect, construction, technical and thinking skills. Students' response to worksheets a very good and good category. From the results of this study concluded that the worksheets based scientific approach has the potential to be implemented on a wider scope.Keywords: Student Worksheets, Thinking Skills, Scientific Approach